Association of dopamine D4 receptor gene variants with autism - Kamal, Maha Moustafa; Nady, Ghada H. El; Abushady, Asmaa M.; Khalil, Mohamed Farouk Mohamed (International Journal of Research in Medical Sciences, 2017)
Background: Autism spectrum disorder (ASD) is a heritable neurodevelopmental disorder with poorly understood and complex etiology. The central dopaminergic system is strongly implicated in ASD pathogenesis. Genes encoding various elements of this system have been linked to ASD. This study aimed to estimate the distribution frequency of dopamine D4 receptor-exon III repeat region polymorphic genotypes among Egyptian children with autism. Methods: This case-control study included 178 children with autism (mean age 4.46±1.72 years) (118 males and 60 females) and a normal control group (n=128) of matching age and gender. Assessments by DSMIV- TR criteria, Stanford-Binet intelligence scale and childhood autism rating scale (CARS) were done. Assay for DRD4 48 bp VNTR genotypes was performed on amplified DNA by RFLP-PCR. Results: The 4/4 allele had the highest frequency among both autistic (39.32%) and control children (62.5%), with no significant difference between them. The 7/7 allele had also a high frequency (33.7%) among autistic patients, which was significantly different (p˂0.05) from the control group (12.5%) Furthermore, 70% of the patients carrying the 7/7 allele had the lowest IQ scores (58.5±6.5). Conclusions: There is a strong evidence that the DRD4 7/7 allele might be a risk factor for autism.